Modelo ProLab: Centro integral para el manejo del estrés - Soto Torres, Mayra Daileny (2025)
This work focuses on proposing a solution to the growth of work stress in Metropolitan Lima, identified as a significant and growing health problem, as evidenced by various national and international studies and reports. Mental health has been highlighted as a predominant problem globally and especially in Peru, where recent studies point to stress as the main mental health challenge among the working population. Thus, the purpose of this thesis project is to design a business model for the creation of a “Comprehensive Center for Stress Management” in Metropolitan Lima aimed at working people. Currently, on the market there are a variety of resources dedicated to stress management, from specialized care from psychologists and psychiatrists, through mental health services offered by EPS and the State, to specialized mental health and well-being centers. However, despite the diversity of options, many workers face challenges that these solutions cannot overcome, such as an isolated and non-comprehensive offer of treatments, high prices, therapies that do not meet their quality expectations, lack of follow-up, and lack of specialized advice to guide them towards an effective and sustainable solution over time. The “Comprehensive Center for Stress Management” will offer its clients a path designed to transform stress into well-being and enhance their quality of life, through the following services: (a) comprehensive diagnosis of stress level, (b) approach of a personalized treatment package that integrates both conventional, alternative and complementary therapies, (c) coordination of all therapies in time and place according to the client's availability, and (d) monitoring and tracking of the participant's achievements, through feedback sessions, tracking the client's progress by adjusting the therapy package as necessary to ensure constant client progress.